Clinical outcomes and in vivo wavefront analysis of a toric transcleral plug-fixated intraocular lens using a pyramidal sensor aberrometer - Lorenzo de Angelis; Vito Romano; Fabrizio Giansanti; Gianni Virgili; Marianna Della Porta; Stanislao Rizzo; Francesco Barca (Journal of Cataract & Refractive Surgery, 2026)
Purpose: To evaluate the visual, refractive, and aberrometric outcomes of a toric (T) FIL–SSF intraocular lens (IOL) implanted in aphakic eyes lacking capsular support. Setting: Ospedale Piero Palagi and Azienda Ospedaliera Universitaria Careggi, Florence, Italy. Design: Multicenter prospective observational case series. Methods: Aphakic eyes with regular corneal astigmatism >1 diopter (D) underwent sutureless transscleral fixation of a T FIL–SSF IOL. Preoperative assessment included uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), manifest refraction, corneal tomography, and biometry. Postoperative visits occurred at 1 day; 7 days; and 1 month, 3 months, and 6 months. At 6 months, vector astigmatism analysis, wavefront aberrometry, and IOL alignment were performed. Results: 15 eyes from 12 patients completed the 6-month follow-up. Mean UDVA improved from 0.96 ± 0.25 to 0.19 ± 0.10 logMAR and CDVA from 0.41 ± 0.32 to 0.04 ± 0.05 logMAR (both P < .01). Mean postoperative spherical equivalent prediction error was −0.12 ± 0.54 D. Mean absolute corneal astigmatism decreased from 2.15 ± 0.54 D to a mean refractive astigmatism of 0.73 ± 0.48 D. Wavefront aberrometry showed total astigmatism of 0.36 ± 0.28 µm, with mean total higher-order aberrations of 0.24 ± 0.08 µm. Mean IOL misalignment was 3.33 ± 3.42 degrees, significantly correlated with residual refractive astigmatism (ρ = 0.71 P < .01). Conclusions: T FIL–SSF IOL implantation provided substantial improvements in visual acuity, predictable refractive outcomes, and significant cylinder reduction in aphakic eyes with corneal astigmatism lacking capsular support.